Microstructure measurement of digital holography - Li, Jicheng (2018)
Miniaturization is a development trend of electronics, machinery and information systems, while micro structure brought a large amount of new development for industrial and research applications, whereas, slow measuring speed and two-dimensional results of traditional micro measurement could not meet our needs, it’s urgent to find a matching testing techniques with more sensitivity, more effectiveness and better to have a real-time three-dimensional display. Digital holography applied to the measurement of micro structure, it made up for the lacking of traditional micro structure measure systems of too much time consuming, poor immunity, easily damaging samples with its simple structure, high accuracy, non contact features and three-dimensional reproduction. This paper analyzed the key factors of digital holographic recording and reproducing process.In order to solve the low quality of holograms captured by traditional recording system, holograms and pre-processing algorithm was combined for real-time, by observing the holograms and delicate adjusting the system, to ensure that the collected holograms with full use of CCD width while convenient for subsequent processing. In the processing of reproduction,the influence of spectrum choice, reconstruction wavelength and algorithms and unwrapping algorithm was been studied, and finally obtained an accurate three-dimensional topography of the object. The improved rerecording system and reconstruction algorithm mentioned above solved the low holography quality, much noise and not clear shortcomings of the reconstructed image. Experiment on a raster, compared with traditional system and algorithm results, results showed that the recording system and determine algorithms can reproduce the three-dimensional topography of the object with high precision and has a broader applicability.